2019
DOI: 10.3390/coatings9100610
|View full text |Cite
|
Sign up to set email alerts
|

Development of Anti-Aging and Anticorrosive Nanoceria Dispersed Alkyd Coating for Decorative and Industrial Purposes

Abstract: This study focuses on nano cerium oxide particles as alternative additives in solvent-based alkyd coatings in order to improve anticorrosive and anti-aging properties. The paint samples were formulated with cerium oxide micro and nanoparticles, and the coating quality characteristics were compared with coating formulated with commercial anticorrosive and UV-aging agents. Formulations were prepared with 3 wt % commercial anticorrosive agent as reference material (RP), 3 wt % cerium oxide microparticles (CER1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Another research concentrated on particles of nano cerium oxide as substitute additives in solvent-based alkyd coatings to enhance anti-anti-ageing and corrosive characteristics (Kızılkonca and Erim, 2019). The authors developed the paint samples with micro and nanoparticles of cerium oxide and thereafter, compared the coating quality properties with coating formulated with commercial UV-aging and anticorrosive agents.…”
Section: Alkyd Resin Metal Nanocomposites Coatingsmentioning
confidence: 99%
“…Another research concentrated on particles of nano cerium oxide as substitute additives in solvent-based alkyd coatings to enhance anti-anti-ageing and corrosive characteristics (Kızılkonca and Erim, 2019). The authors developed the paint samples with micro and nanoparticles of cerium oxide and thereafter, compared the coating quality properties with coating formulated with commercial UV-aging and anticorrosive agents.…”
Section: Alkyd Resin Metal Nanocomposites Coatingsmentioning
confidence: 99%
“…The oxidation state transition between Ce 3+ and Ce 4+ found on the surface of CeO 2 -NPs is responsible for the catalytic activity of this nanoparticle. Although the toxicity of nanoparticles is still a questionable issue, it has been shown by experiments that CeO 2 -NPs are not toxic, and these nanoparticles are compatible with hydrogels and impart durability and antibacterial properties to wound-healing hydrogels and anticorrosive properties to paints. In addition, it has been shown that CeO 2 nanoparticles synthesized by the green method gain additional and different surface properties. , The effective use of CeO 2 -NPs obtained by the green method in dye photodegradation has been lately demonstrated …”
Section: Introductionmentioning
confidence: 99%
“…Degradation of polymers in general or paint coating in particular under high temperature, oxygen, sunlight, UV radiations, and humidity leads to losing adhesion, blistering or peeling [1][2][3][4][5]. Jianwen Hu et al [6] showed the degradation of acrylic polyurethane varnish coating under fluorescent UV/condensation and xenon lamp exposure.…”
Section: Introductionmentioning
confidence: 99%